The Non-radicalisation of Muslims in Southern Europe - Magazzini, Tina. author. (orcid)0000-0001-8534-0175 Link aut Link
XV, 124 p. 8 illus., 7 illus. in color.
Keywords: This open access book explains why southern European countries with significant Muslim communities have experienced few religiously inspired violent attacks – or have avoided the kind of securitised response to such attacks seen in many other Western states. The authors provide a unique contribution to the literature on violent extremism – which has traditionally focused on countries such as France, the US and the UK – by studying the causes of relatively low rates of radicalisation in Greece, Italy and Spain. The book explores many of the dynamics between (non) radicalisation and issues such as socioeconomic inequality, experiences of conflict, and systemic racism and other forms of discrimination. It establishes a new analytical framework for the development of, and resilience against, violent radicalisation in the region and beyond. Tina Magazzini is a Distinguished Fellow at the University of A Coruña, a Research Associate at the Interuniversity Centre for Atlantic Cultural Landscapes and at the Czech Academy of Sciences. Marina Eleftheriadou is Assistant Professor at Neapolis University Pafos and Consulting Editor at the Centre for Mediterranean, Middle East and Islamic Studies. Anna Triandafyllidou is a Full Professor and holds the Canada Excellence Research Chair in Migration and Integration at Toronto Metropolitan University.